Dependency scanner - Low, Zi Qing (2018)
The methodology to develop software applications is changing throughout the years. Developers depend heavily on software libraries to implement the functionalities. Understanding the importance of software security mitigates or prevents software applications from being exploited. Applications are built with only solutions in mind, where the security aspects were neglected. Hence, the study of enhancing computers security system is important. In this report, the author presented his implementation of Open Web Application Security Project (OWASP) Dependency Check to detect vulnerabilities in Java Applications and Web Application Resource. The research was conducted on how to improve the search performances for the scan. This was done by creating test cases to scan various Java Applications to determine the execution time and finding new methods to reduce the time taken. Reducing false positive and negative to increase the accuracy of the results.